Shear wave elastography can assess the in-vivo nonlinear mechanical behavior of heel-pad - Chatzistergos, Panagiotis E.; Behforootan, Sara; Allan, David; Naemi, Roozbeh; Chockalingam, Nachiappan (Journal of biomechanics, 2018)
This study combines non-invasive mechanical testing with finite element (FE) modelling to assess for the first time the reliability of shear wave (SW) elastography for the quantitative assessment of the in-vivo nonlinear mechanical behavior of heel-pad. The heel-pads of five volunteers were compressed using a custom-made ultrasound indentation device. Tissue deformation was assessed from B-mode ultrasound and force was measured using a load cell to calculate the force – deformation graph of the indentation test. These results were used to design subject specific FE models and to inverse engineer the tissue’s hyperelastic material coefficients and its stress – strain behavior. SW speed was measured for different levels of compression (from 0% to 50% compression). SW speed for 0% compression was used to assess the initial stiffness of heel-pad (i.e. initial shear modulus, initial Young’s modulus). Changes in SW speed with increasing compressive loading were used to quantify the tissue’s nonlinear mechanical behavior based on the theory of acoustoelasticity. Statistical analysis of results showed significant correlation between SW-based and FE-based estimations of initial stiffness, but SW underestimated initial shear modulus by 64%(±16). A linear relationship was found between the SW-based and FE-based estimations of nonlinear behavior. The results of this study indicate that SW elastography is capable of reliably assessing differences in stiffness, but the absolute values of stiffness should be used with caution. Measuring changes in SW speed for different magnitudes of compression enables the quantification of the tissue’s nonlinear behavior which can significantly enhance the diagnostic value of SW elastography.